A pressure-coupled Drucker function for plasticity and fracture modelling of AA5182. Issue 1 (November 2020) - Zhang, Chong; Wang, Yue; Lou, Yanshan; Fu, Lei; Zhang, Saijun; Yoon, Jeong Whan
Abstract: In this paper, a pressure-coupled Drucker function is proposed to model the plastic deformation and fracture from shear to plane strain tension of AA5182 sheet. Experiments are conducted for AA5182 in shear, uniaxial tension and plane strain tension, and the force-stroke curves are measured during the tests. The plastic deformation is modeled by the Drucker function. The Drucker function is modified to consider the pressure effect for fracture limit stress prediction of the alloy. The pressure-coupled Drucker function for plasticity and fracture is calibrated by an inverse engineering approach. The calibrated plasticity models are then applied to numerical prediction of plastic deformation of the alloy under various loading conditions. It is observed that the pressure coupled Drucker function accurately describes the plastic deformation under large plastic deformation as well as the onset of ductile fracture under these loading conditions.